Early Management Experience of Perforation after ERCP - Guohua Li; Youxiang Chen; Xiaojiang Zhou; Nonghua Lv (Gastroenterology Research and Practice)
Background and Aim. Perforation after endoscopic retrograde cholangiopancreatography (ERCP) is a rare complication, but it is associated with significant mortality. This study evaluated the early management experience of these perforations. Patients and Methods. Between November 2003 and December 2011, a total of 8504 ERCPs were performed at our regional endoscopy center. Sixteen perforations (0.45%) were identified and retrospectively reviewed. Results. Nine of these 16 patients with perforations were periampullary, 3 duodenal, 1 gastric fundus, and 3 patients had a perforation of an afferent limb of a Billroth II anastomosis. All patients with perforations were recognized during ERCP by X-ray and managed immediately. One patient with duodenal perforation and three patients with afferent limb perforation received surgery, others received medical conservative treatment which included suturing lesion, endoscopic nasobiliary drainage (ENBD), endoscopic retrograde pancreatic duct drainage (ERPD), gastrointestinal decompression, fasting, broad-spectrum antibiotics, and so on. All patients with perforation recovered successfully. Conclusions. We found that: (1) the diagnosis of perforation during ERCP may be easy, but you must pay attention to it. (2) Most retroperitoneal perforations can recover with only medical conservative treatment in early phase. (3) Most peritoneal perforations need surgery unless you can close the lesion up under endoscopy in early phase.